Hey, I don't undertand how to solve this equation using substitution.

3y = -1/2x + 2
y= x + 9

1 answer

sub the 2nd into the 1st

3y = (1/2)x + 2
3(x+9) = (-1/2)x + 2
3x + 27 = (-1/2)x + 2
times 2 to get rid of that nasty fraction

6x + 54 = -x + 4
7x = -50
x = -50/7

then y = x+9 = -50/7 + 9 = 13/7

check:
in #1:
3y = (-1/2)x + 2
LS = 3(13/7) = 39/7
RS =(-1/2)(-50/7) + 14/7
= 25/7 + 14/7 = 39/7 = LS

my answer is correct.
Similar Questions
  1. Solve the system of equations by SUBSTITUTION.6y+5x=8 x+3y=−7 (1 point) ​What would your equation look like after the first
    1. answers icon 1 answer
  2. Use the Substitution method to solve the system of equations.x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put
    1. answers icon 5 answers
    1. answers icon 3 answers
    1. answers icon 30 answers
more similar questions